Perbandingan Variasi Spesies Capung (Odonata) di Dua Daerah Habitat Berbeda Bukit Sulap dan Bukit Cogong - Destien Atmi Arisandy; Dian Samitra; Merti Triyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the diversity of dragonflies (Odonata) in two different habitats, namely Bukit Sulap in Lubuklinggau City and Bukit Cogong in Musi Rawas Regency. The method used was an exploratory survey with a comparative approach through direct field observations. The data collected included species types and habitat characteristics. The results showed that Bukit Cogong had nine dragonfly species, while only one species was found in Bukit Sulap. This difference is caused by variations in habitat quality, particularly the availability of clean water, vegetation structure, and the level of anthropogenic disturbance. Bukit Cogong, which is more natural, supports the dragonfly life cycle optimally, whereas Bukit Sulap experiences pressure from tourism activities that affect the abundance and diversity of dragonflies. In conclusion, Odonata can be used as an ecological indicator to assess environmental health and the level of disturbance in an ecosystem. Keywords: Bukit Cogong, Bukit Sulap, Diversity, Habitat, Odonata